Uji Perbedaan Kualitas Organoleptik Dendeng Babi yang Dikeringkan dengan Oven dan Dijemur - Astrid Alviani Sau; Larry R. W. Toha; Meity M. Laut (JURNAL KAJIAN VETERINER, 2023)
Pigs are meat-producing livestock that are widely raised in the community, as one of animal protein source for the human body. Pork can be processed into various kind of food, one of which is pork jerky. Jerky can be made using sliced ​​or ground pork. Jerky can be dried traditionaly (sun dried) or more advanced way (oven dried). The purpose of this study was to determine the effect of different drying methods on the organoleptic quality of pork jerky. The results based on paired t-test analysis showed that there was no significant difference (P>0,05) between the smell, texture and acceptability of pork jerky with different drying treatments. Meanwhile, the analysis of the color and taste of pork jerky showed a significant difference (P<0,05) between the two treatments. Although statistically there are differences between two drying treatments, the average number show a very small the differences. In conclusion, both oven-dried and sun-dried pork jerky are acceptable and suitable for consumption.